THE POSITION OF FIFA REGULATION IN THE SPORTS REGULATION SYSTEM IN INDONESIA - Abdurrahman, Abdurrahman; Phahlevy, Rifqi Ridlo (Journal of Geography, Regional Planning and Development, 2024)
In various football problems, there is one classic problem that usually occurs in Indonesia, namely players' salaries that have not been paid or there are arrears in players' salaries. For example, the case of Bambang Pamungkas and Leo Saputra who filed a civil lawsuit against the Persija Jakarta club following the salary settlement which had been in arrears for more than a year at the Central Jakarta District Court with lawsuit number: 523/PDT.G/2013/PN.JKT.PST and PDT.G/2013/PN.JKT.PST. As well as Budi Sudarsono who is suing the Sidoarjo Deltas team whose salaries have not been paid since 2011. It is contained in a civil complaint at the Sidoarjo District Court case number 216/Pdt.G/2022/PN Sda. This case is one of the problems of resolving a dispute between the player's rights and the club's obligations as agreed at the beginning of the agreement between both parties. With the player's rights not being fulfilled as in the case above, the authority to resolve the dispute is whether through the courts or adhering to the main regulations of the football organization in Indonesia, in this case the All Indonesian Football Association, hereinafter referred to as PSSI which is part of the International Federation. Football Association, hereinafter referred to as FIFA. In this case example, if a football player prefers to settle through the courts, then the problem will arise whether the court decision can be a final decision and what is the authority of the district court in deciding disputes between players and football clubs considering that in professional football there is the principle of lex sportiva which regulates law independently.